Association of dietary glycemic index and glycemic load with serum lipids level in women with polycystic ovary syndrome - Farzaneh Shahrdami; Beitolah Alipour; Elham Roohelhami; Bahram Rashidkhani (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2020)
Introduction: Polycystic ovary syndrome (PCOS) is a common endocrinopathy among women and insulin resistance is one of the clinical features in this syndrome which plays an important role in improvement of lipid disorders. Dietary glycemic index and glycemic load can affect blood lipid disorders. Because of limited studies in this field, this study was performed with aim to evaluate the relationship between dietary glycemic index/glycemic load and serum lipids level in women with PCOS. Methods: This case-control study was conducted on 45 PCOS women and 45 healthy controls in Moheb Yas Women hospital of Tehran in 2016. Dietary intake was assessed using three 24-h recall questionnaires, and glycemic index and glycemic load were calculated by standard methods. Lipid profile was measured and insulin resistance was calculated by the formula. Anthropometric measurements were conducted in all participants. Data were analyzed by SPSS software (version 16), and Independent T-test and correlation test. P< 0.05 was considered statistically significant. Results: Mean of serum total cholesterol, insulin resistance and mean of glycemic index was significantly higher in the patients group than the control group (P<0.05). There was a significant relationship between glycemic load and insulin resistance, triglyceride and HDL-c in patients (r=0.388, r=0.401, r= -0.371, respectively (P<0.05). No significant relationship was found between glycemic index with biochemical markers in patients and controls (P>0.05). Conclusion: Lifestyle modification like correct nutritional status and management of carbohydrate intake and reducing the dietary glycemic load may be effective in prevention or reducing the complications of disease such as lipid abnormalities.